Effects of iron-chelation therapy intensification on glucose homeostasis during 3-h oral glucose tolerance test (OGTT) in transfusion-dependent β-thalassemia patients (β-TDT) - De Sanctis, Vincenzo; Daar, Shahina; Soliman, Ashraf; Campisi, Saveria; Tzoulis, Ploutarchos (Acta Biomedica Atenei Parmensis, 2024)
Background: Iron overload (IOL) due to chronic transfusion therapy in β-thalassemia major (β-TDT) patients leads to multi-organ damage, including glucose dysregulation (GD). The effectiveness of intensified iron chelation therapy (ICT) on glucose homeostasis and its ability to reverse iron-induced endocrinopathies is not fully understood. Objectives: To assess the effects of intensified ICT on glucose homeostasis, insulin secretion, and sensitivity in adolescent and very young adult β-TDT patients with moderate to severe IOL. Methods: This retrospective study evaluated 19 β-TDT patients who underwent intensified ICT with the aim of reducing serum ferritin (SF) to 500-1,000 ng/mL. Over a median follow-up of 4.2 years, parameters including oral glucose tolerance test (OGTT), insulin response, and serum ferritin levels were analyzed. Results: Despite a marked reduction in SF and IOL, the prevalence of GD remained unchanged (P= 0.75). Some patients showed improvement in glucose tolerance, whereas other developed new endocrine disorders, such as hypogonadotropic hypogonadism and secondary amenorrhea. Improvements were seen in insulin sensitivity, but not in pancreatic β-cell function. Conclusion: Intensified ICT in β-TDT patients, albeit effectively reducing iron burden, did not uniformly reverse established glucose homeostasis disorders. While some endocrine functions improved, others deteriorated or developed a new complication, suggesting that more aggressive or prolonged ICT may be necessary. Long-term studies are required to better understand the impact of ICT on endocrine organ function. (www.actabiomedica.it)